Social Marketing Strategies for Renewable Energy Transitions. Issue 2 (May 2017) - Eagle, Lynne; Osmond, Amy; McCarthy, Breda; Low, David; Lesbirel, Hayden
Transitions to more sustainable energy systems are increasingly required to address the problem of climate change. Different stakeholder groups, however, may not share the same level of acceptability for an increase in renewable energy. This paper examines energy consumers' attitudes towards energy issues, their use of renewable energy in the home and constraints to energy conservation. Respondent-completed questionnaires from 325 people reveal strong support for renewable energy and a belief in human-induced climate change. A multitude of obstacles to energy-efficient practices are revealed by the survey. The paper also explores the role of social marketing in prompting behavioural change and encouraging a transition to renewable energy. Policy makers can utilise these findings to accelerate the transition to renewable energy and build capacity among residents.